Factors influencing the intention to buy microinsurance: A case study of low-income customers in Ho Chi Minh City - Phan , Thanh Tam; Luu, Phi Nga (Journal of Finance - Marketing Research, 2024)
Microinsurance is a form of insurance for low-income people that is being expanded in developing countries, including Vietnam. In addition, microinsurance plays the financial protection and savings role for individuals and families with low income, ensuring social security and sustainable economic development. Therefore, the article aims to determine critical factors influencing low-income customers' intention to buy microinsurance in Ho Chi Minh City. On that basis, the authors propose that the implication of corporate governance contributes to increasing the intent to purchase microinsurance products/services. In the research paper, the authors used a qualitative method by interviewing five managers of five companies related to insurance, finding five factors related to the research topic. Quantitative research was carried out with a sample of 400 customers with low income, using multivariate linear regression analysis, and five factors with a significance level of 5 percent were identified. Finally, the authors have proposed five governance implications in order of priority: Safety, social influence, convenience, ease of use, and benefits. Research applications contribute to orientation for insurance organizations to improve the quality of microinsurance products/services to better serve customers and other low-income people.